1991
DOI: 10.1111/j.1365-2761.1991.tb00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of Yersinia ruckeri based on biotypes, serotypes and outer membrane protein‐types

Abstract: The biotypes, serotypes and outer membrane protein-types (OMP-types) of 135 isolates of Yersinia ruckeri were analysed in an attempt to identify elonal groups and to examine in further detail the relationships between isolates from wide geographie areas. Eaeh isolate eould be assigned to one of two biotypes (1 and 2), one of five 0-serotypes (01, 02, 05, 06 and 07), and one of live OMP-types (1-5). Outer membrane protein analysis was able lo differentiate between isolates within a given serotype. Thus, serotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 19 publications
2
50
0
Order By: Relevance
“…In general, the highly clonal nature of Yersinia ruckeri isolates responsible for ERM in rainbow trout, as shown by this and other studies (Pyle et al 1987, Davies 1991a, Garcia et al 1998, is similar to that observed for other significant bacterial pathogens of farmed fish (Grayson et al 1999, Eyngor et al 2004, Reid et al 2004, Nash et al 2006. Although the isolates analysed were geographically biased and, in many cases, nonrandomly selected (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In general, the highly clonal nature of Yersinia ruckeri isolates responsible for ERM in rainbow trout, as shown by this and other studies (Pyle et al 1987, Davies 1991a, Garcia et al 1998, is similar to that observed for other significant bacterial pathogens of farmed fish (Grayson et al 1999, Eyngor et al 2004, Reid et al 2004, Nash et al 2006. Although the isolates analysed were geographically biased and, in many cases, nonrandomly selected (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…The majority of ERM-causing serotype O1 isolates in the UK has always been biotype 2 (Davies & Frerichs 1989, present study). In contrast, Danish biotype 2 serotype O1 isolates shared the same pulsotype (pt35) as the serotype O1 biotype 1 clone (clonal group 5), the latter being responsible for the majority of disease outbreaks since the first emergence of ERM in Denmark and elsewhere in mainland Europe (Davies 1991a). It is therefore likely that the Danish biotype 2 isolates have independently emerged out of the existing mainland European Y. ruckeri population, rather than representing cross-border transfer of UK biotype 2 isolates into or from Denmark.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible relation between motility and virulence is at present unknown and needs further investigation. Davies (1991b) also found different clonal groups within serotype 0 1 according to biotypes, serotypes and OMP profiles. This author reported that two of these clonal groups were predominant, one in the UK and the other in the rest of Europe.…”
Section: Discussionmentioning
confidence: 72%